Risk factors for nosocomial infection in patients undergoing extracorporeal membrane oxygenation support treatment: A systematic review and meta-analysis. - Xiangui Lv; Yan Han; Daiqiang Liu; Xinwei Chen; Lvlin Chen; Huang Huang; Chao Huang (PLoS ONE)
Objective To evaluate the risk factors of nosocomial infection during Extracorporeal membrane oxygenation (ECMO) treatment through systematic evaluation and meta-analysis, in order to provide evidence-based basis for clinical treatment and prevention of nosocomial infection during ECMO treatment. Method Computer search of Cochrane Library, PubMed, Embase, and Web of Science databases was conducted to establish a database of relevant literature published in March 2023. Two researchers independently screened literature, extracted data, and evaluated quality based on inclusion and exclusion criteria, and then analyzed the data using STATA 14.0 software. This plan is registered with PROSPERO as CRD42021271083. Result A total of 2955 ECMO patients, including 933 nosocomial infected patients, were included in 23 articles. Meta analysis showed that immunosuppression, Heart transplantation, VA-ECMO, CRRT, red blood cell input, ECMO support time, mechanical ventilation time, ICU hospitalization time, and total hospitalization time were the risk factors for nosocomial infection in patients supported by ECMO. Conclusion ECMO treatment for nosocomial infections in patients is related to multiple factors. In clinical work, medical staff should identify high-risk groups of ECMO nosocomial infections, actively take preventive measures, and reduce the incidence and mortality of nosocomial infections.